RISKS AND CONSEQUENCES OF EARLY FOOD INTRODUCTION: AN INTEGRATIVE REVIEW (Editora Impacto Científico, 2025)
Early introduction of solid foods—before six months of age—is considered a risk factor for child health, as it compromises the ideal supply of nutrients and increases vulnerability to disease. This integrative review aimed to identify the main risks and consequences associated with early introduction of solid foods. Twelve articles published in the last five years were analyzed, selected from the Scielo and Google Scholar databases using the keywords: "early feeding," "child health," "consequences," and "risks." The studies indicated that 70% of the evidence points to a reduction in the bioavailability of essential nutrients, in addition to an increase in allergies, gastrointestinal infections, and childhood obesity. It was concluded that, although introducing food at six months does not eliminate all risks, following age recommendations, together with family-oriented nutritional education, is essential to ensure a safe dietary transition and promote child health.